PENGARUH PENERAPAN STRATEGI RODA KEBERUNTUNGAN TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMPN 1 KINALI KABUPATEN PASAMAN BARAT - Silvia, Alisa; Nurhadi, Nurhadi; Maizeli, Annika (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ The studentsâ lack of motivation in learning was assumed as the cause of their low achievement in Biology. One of the efforts done to improve the studentsâ learning achievement was by applying Luck Wheel strategy. This research was aimed at revealing the effect of applying Luck Wheel strategy on the studentsâ learning achievement in Biology in class VII of SMPN 1 Kinali in Academic Year 2012/2013. This was an experimental research which used Control-Group Posttest Only Design. The population of the research was all of students in class VII of SMPN 1 Kinali registered in Academic Year 2012/2013. By using purposive random sampling technique, class VII1Â was chosen as the experimental class and class VII6Â as the control class. The result of the research indicated that after the strategy applied, the average score of the experimental class was higher than the control one in which the score for the experimental class was 77,6 and the control one was 68,0. Based on the result of hypothesis test it was concluded that the use of Luck Wheel strategy could improve the students learning achievement in Biology especially in Ecosystem topics at SMPN 1Kinali Kabupaten Pasaman Barat.Â